Analisis Kesesuaian WCAG terhadap Website Pemerintah Daerah dengan Nilai SPBE 2022 Tertinggi menggunakan Tools Accessibility Checker - Baiq Nurul Azmi; Aziz Perdana; Suhirman; Sutarman (KITA Institute, 2023)
From 2017 to 2022, the Department of Administrative and Bureaucratic Reform assessed the SPBE index of various government agencies with the aim of improving public services and community engagement through technology. In this context, assessing the accessibility of a website or an information system is a simple way of assessing the convenience for the public to access a website or a government information system. government. This study aims to test the accessibility of websites belonging to the three district/city governments with the highest SPBE scores in 2022, Surakarta City, Surabaya City and Denpasar City in terms of usage. WCAG standards. The tests were performed using three accessibility automation tools, namely aXe, WAVE and siteImprove. As a result, despite their high SPBE scores, Surabaya and Surakarta still had a number of accessibility issues that needed to be resolved.